Kafka in the Realm of Sensitivity of Julio Ramón Ribeyro - Esteban, Ángel (2023)
Specialized critics have so far insisted on the impact of Kafka as a narrator on Ribeyro’s stories, consistently in the same direction: it would be a direct influence on the stories written in the late forties and early fifties, texts from his youth with some fantastic or absurd element, and during a formative period in which the man from Lima had not yet developed his own voice. However, the most intense and profound presence of Kafka in Ribeyro is found in his diaries, and not so much in the themes or style, but in the common characteristics of “spiritual kinship” embedded in the realm of sensitivity and in how they both construct themselves as artists.